TERMS ANALYSIS REFERRING TO THE PROFESSIONAL COMMUNICATION TRAINING OF FUTURE PHYSICIANS - Manyuk, Lyubov; Kuchumova, Nataliya (Continuing Professional Education: Theory and Practice, 2019)
The article presents the main findings of carried out terminological analysis of the professional communication training in undergraduate medical education and describes developmental factors influ-encing the communication skills development with the aim of further accounting received results in the process of modernizing subjects directed at the formation of professional qualities and communicative competence of medical students. The definition of the terms referring to the medical communication training enabled us to determine professional communication of future physicians that develops under the influence of linguistic, psychological, educational and professional factors. The communication readiness includes the development of professional and communication competencies which are realized in the current system of higher medical education by the staged professional undergraduate training and subjects aimed at gaining clinical, linguistic, social and cultural skills. Thus, communicative competence involves the development of lexical and grammatical competencies in both Ukrainian and foreign languages as well as the formation of ethical values in order to provide effective monologues, dialogues and polylogues during the interpersonal and intrapersonal interaction in colloquial, official, business, academic and teaching speaking styles. Modern pedagogical approaches to the professional communication training and global academic processes necessitate the application of information and communication technologies in the educational process physicians and their further carrier. The subjects directed at the development of communicative competencies of medical students should encompass theoretical and practical aspects of professional clinical thinking and proper language skills; acquiring clinical skills; development of social and professionally important qualities and values; learning the key aspects of professional activity with the aim to force the readiness for professional communication by means of professional language in the determined forms of communication.